Padrões estacionais de preços de produtos agropecuários no Estado do Espírito Santo - Melges Walder , Vladimir; Brandt, Sergio Alberto; Moreira Leite , Carlos Antônio; Dantas Landim , Alfredo (Revista Ceres, 2025)
Seasonal price analysis might be an important tool for market policy. The objective of this study is the analysisof seasonal price patterns for six important farm products of the State of Espírito Santo. The products studied were: paddy rice, corn, green coffee, beans, bananas and cassava. Twelve months moving averages of prices paid to farmers were used as basic information.